The World Bank Annual Report 2009 : Year in Review, Volume 2. Financial statements - World Bank (Washington, DC, 2012)
The World Bank group, among the world's largest development institutions, is a major source of financial and technical assistance to developing countries around the world. In fiscal 2009, the World Bank group sponsored 767 projects with a total commitment of $58.8 billion, distributed in credits, loans, grants, and guarantees. This fiscal year's funding marks a 54 percent increase over the previous fiscal year and a record high for the Bank group. The Bank group's investment projects are aimed largely at improving infrastructure services associated with poverty reduction and enhanced growth. In fiscal 2009, the Bank group committed $20.7 billion to infrastructure, a critical sector to provide the foundation for rapid recovery from the crisis and to support job creation. The sustainable infrastructure action plan, launched in July 2008, will leverage up to $72 billion to provide additional financing of up to $149 billion in public and private investments over fiscal 2009-11. The Bank group's investment projects are aimed largely at improving infrastructure services associated with poverty reduction and enhanced growth.